Pembelajaran Kecerdasan Kinestetik dan Kecerdasan Visual Spasial pada AUD di TK IT Siti Khadijah - Fauziah Nasution; Dwi Nur Atira Ain; Nabila Nabila; Salsabila Wibowo; Sara Ningtya Ayu (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the implementation of kinesthetic and visual-spatial intelligence learning in early childhood. The background of this research is the importance of developing multiple intelligences in early childhood, especially kinesthetic and visual-spatial intelligence which often receive less attention in formal learning. The research methods used include limited participatory observation, in-depth interviews with teachers, and documentation of children's work and lesson planning documents. The results of the research at TKIT Siti Khadijah show that the learning activities designed consistently support the development of children's multiple intelligences. A case study of a child named Abbil showed significant progress in visual-spatial intelligence through coloring activities, assembling lego blocks, and basic introduction to visual programming. In the kinesthetic aspect, Abbil showed good body coordination through morning exercises and traditional games such as engklek, as well as social-kinesthetic skills in group games. This study concludes that developing kinesthetic and visual-spatial intelligence through a holistic and fun learning approach can help children reach their full potential.